Cultural and Contemporary Perspectives of Iqtar Javed’s Poem - Mehmood, Arshad; Rehana, Fariha; Abbas, Syed Azwar (sourcecoder, 2023)
Iqtadar Javed is one of the modern Urdu poets. Iqtadar has illustrated natural scenes in his poems in a very good way. His poems are a model of depiction of nature and dynamic sculpting. In his poems, social issues are included in a natural way. A special feature of Iqtar Javed’s poems is that they are written somewhere in between. The present and non-existent. In terms of modern poetry, Iqtar Javed has emerged as an important poet. Iqtar Javed is deeply aware of contemporary requirements. Social inequalities are reflected in his poetry. Iqtar Javed has also given the spirit of nationalism a poetic form.